Comparison of rhizobacterial communities between secondary forest and palm oil plantations in East Kalimantan, Indonesia - ERVINDA YULIATIN; NOVA HARIANI; BODHI DHARMA; FATMAWATI PATANG; BUDIMAN BUDIMAN (Society for Indonesian Biodiversity, 2025)
Abstract. Yuliatin E, Hariani N, Dharma B, Patang F, Budiman. 2025. Comparison of rhizobacterial communities between secondary forest and palm oil plantations in East Kalimantan, Indonesia. Biodiversitas 26: 490-499. The conversion of primary forests to plantations is considered a sustainable form of land management; however, its implications for soil rhizobacterial diversity remain insufficiently explored. This study compared the rhizobacterial communities associated with Palm oil Plantation (PP) and Secondary Forest (SF) in East Kalimantan using a metagenomic approach. The soil samples were collected around the Secondary Forest soil (SF) and Palm oil Plantation soil (PP) plant roots in Berambai, Samarinda. The samples were then analyzed for soil physico-chemical properties such as pH, nitrogen (N), phosphorus (P), potassium (K), organic matter, and C/N ratio. At the same time, the rhizobacterial diversity was analyzed using a metagenomic analysis through Illumina Hiseq. Soil physico-chemical assessments showed acidic conditions in both soils, with PP being more acidic (pH 4.41) than SF (pH 5.38); nutrient analysis indicated medium nitrogen levels and high organic carbon in both soils, while PP had elevated P content due to fertilization. Metagenomic analysis revealed similar rhizobacterial richness, but diversity was slightly higher in PP. Dominant phyla included Proteobacteria and Acidobacteriota, with notable orders like Rhizobiales and Acidobacteriales. The functional analysis highlighted rhizobacterial roles in organic decomposition, plant growth promotion, and nitrogen fixation, illustrating ecological adaptation to soil conditions and management practices. This study provides insights into the rhizobacterial functional diversity in distinct soil environments.